DigiWise: An Interactive Narrative Game for Enhancing Digital Security Literacy among Junior High School Students - Yumna Ashri Nabilah; Nuur Wachid Abdul Majid; Assyifa Azzahra Muthmainnah (Journal of Educational Sciences, 2026)
The high rate of internet penetration in Indonesia among adolescents (78.19%) has not been matched by adequate digital security awareness, while existing learning media remain passive and unable to simulate digital threats contextually. This study aims to develop DigiWise, an interactive story game based learning medium using Unity 2D to enhance digital security literacy among Junior High School students. The method employed is Research and Development with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The novelty of this research lies in the integration of the Danger Level mechanism within the Choice Based Narrative system, which provides  educational feedback based on risk levels in real time. Product feasibility was assessed by two expert validators using a Likert scale 1–5 questionnaire. The media expert assigned 76.7% (Feasible) and the content expert assigned 93.3% (Highly Feasible), yielding a combined average of 85% (Highly Feasible). These results confirm that DigiWise is feasible as a digital security learning medium for junior high school students. However, this study is limited to expert validation and has not yet examined the effectiveness of DigiWise on students digital security literacy.